2014
DOI: 10.1002/adfm.201403436
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Iron Oxide Nanowhiskers as Positive Contrast Agents for Magnetic Resonance Imaging

Abstract: In this paper, a highly innovative concept of using ultrathin iron oxide nanowhiskers as a positive (T1) contrast agent for magnetic resonance imaging (MRI) is demonstrated. Iron oxide nanowhiskers with dimensions of approximately 2 nm × 20 nm are synthesized by heating an iron oleate/oleylamine complex under 150 °C. These nanostructures have very high surface‐to‐volume ratios, leading to strong paramagnetic signal, a property suitable for T1 contrast in MRI. The positive contrast enhancement of these nanowhis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…9), we believe further improvements are possible by, e.g., templating directional growth to form morphological variations like octapods, 23 bricks, 24 or whiskers; 25 or subjecting them to controlled aggregation and/or self-assembly, which are known to lead to higher contrasting abilities.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…9), we believe further improvements are possible by, e.g., templating directional growth to form morphological variations like octapods, 23 bricks, 24 or whiskers; 25 or subjecting them to controlled aggregation and/or self-assembly, which are known to lead to higher contrasting abilities.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…17,18 Recently, it has been reported that non-spherical iron oxide nanoparticles (NPs) could greatly improve their usefulness for biomedical applications. 6,[19][20][21] Of particular importance, iron oxide nanocubes demonstrate extremely high r 2 relaxivity as negative magnetic resonance imaging (MRI) contrast agents 20 and a high value of the specific absorption rate necessary for hyperthermia cancer treatment. 21 Further, doping of other inorganic ions offers a great way to adjust the physical properties of magnetic ferrite nanoparticles and their usefulness in applications.…”
Section: Introductionmentioning
confidence: 99%
“…Red circle indicates the bleb at the site of injection. Copyright © Royal Chemical Society 2015 [29]. …”
Section: Figurementioning
confidence: 99%
“…Recently, it has been shown that non-spherical iron oxide nanoparticles could improve their usefulness for biomedical applications. For examples, ultrathin iron oxide nanowires can serve as effective T 1 MRI contrast agents [29]. Iron oxide nanoworm-like particles formed by aggregation of spherical nanoparticles showed increased blood circulation time and more effective targeting [30].…”
Section: Introductionmentioning
confidence: 99%